2007
DOI: 10.1161/01.hyp.0000253258.36141.c7
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Adrenal Steroids With Hypertension and the Metabolic Syndrome in Blacks

Abstract: Abstract-Blacks have a high prevalence of hypertension and adrenal cortical adenomas/hyperplasia. We evaluated the hypothesis that adrenal steroids are associated with hypertension and the metabolic syndrome in blacks. Ambulatory blood pressures, anthropometric measurements, and measurements of plasma renin activity (PRA), aldosterone, fasting lipids, glucose, and insulin were obtained in 397 subjects (46% hypertensive and 50% female) after discontinuing antihypertensive and lipid-lowering medications. Hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
142
3
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(160 citation statements)
references
References 56 publications
9
142
3
5
Order By: Relevance
“…Metabolic syndrome, especially adipocytokines secreted from pathological adipocytes and aldosterone, seem to have mutual physiological effects, and both are important to understanding the pathology of obesity, hypertension and metabolic syndrome. [33][34][35][36][37] The adipose tissue is fundamentally rich in glucocorticoid receptors coexisting with 11b-hydroxysteroid dehydrogenase type 1 (11-HSD1), and has been believed to be the glucocorticoid target tissue. [38][39][40] However, recently, adipose tissue was reported to also contain MR, 41 although much remains to be elucidated, including the role of MR in adipose tissue and its physiological ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome, especially adipocytokines secreted from pathological adipocytes and aldosterone, seem to have mutual physiological effects, and both are important to understanding the pathology of obesity, hypertension and metabolic syndrome. [33][34][35][36][37] The adipose tissue is fundamentally rich in glucocorticoid receptors coexisting with 11b-hydroxysteroid dehydrogenase type 1 (11-HSD1), and has been believed to be the glucocorticoid target tissue. [38][39][40] However, recently, adipose tissue was reported to also contain MR, 41 although much remains to be elucidated, including the role of MR in adipose tissue and its physiological ligands.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Hall et al 19 reported a more than twofold increase in plasma renin activity after a 5-week period of highfat diet administration in conscious dogs. Moreover, fat restriction succeeded in diminishing the values of the RAS components, indicating the possibility that the degree of adiposity might have a direct influence in this BP-regulating system.…”
Section: Function Of Ras In Obesity Hypertensionmentioning
confidence: 99%
“…Kidambi et al 16 showed that PAC correlated positively with blood pressure, waist circumference and insulin resistance index in patients with hypertension and the metabolic syndrome, whereas plasma potassium levels and PRA were similar in patients with the metabolic syndrome and in those without. Bentley-Lewis et al 14 reported that urinary aldosterone excretion and Ang II-stimulated aldosterone were increased in overweight patients compared with that in lean, normotensive patients, although PRA, urinary cortisol excretion and plasma potassium levels did not differ between the two groups.…”
Section: Mineralocorticoid-stimulating Factorsmentioning
confidence: 99%